Primer reporte del escarabajo Acanthoderes funeraria (Bates) (Coleoptera: Cerambycidae) en el agave silvestre Agave cupreata (Trel. & Berger) en Guerrero, México - Sánchez-Jiménez, Eduardo; Orbe-Díaz, Diana Iveth; Romero, Yanet; Toribio-Jiménez, Jeiry (Instituto de Ecología, A.C., 2019)
Acanthoderes funeraria, is a beetle that feeds on the leaves of agave plants and causes serious and irreversible damage to plants. A collection of insects was made on June 20, 2018, in the town of Petaquillas, Guerrero. Young and adult sick plants were checked, then 60 specimens were collected by hand and photos were taken and images were sent to CONABIO for identification, which confirmed the species as A. funeraria and it recorded the presence in the state of Guerrero; other specimens were deposited in the Entomological Collection of the Faculty of Biological Sciences of the Autonomous University of Guerrero with registration number 020219fcqb. This beetle for the first time is recorded on wild agaves of A. cupreata in the state of Guerrero, Mexico; moreover, the damage to the plants is described.